A MULTINOMIAL APPROACH FOR ORGANIC AGRICULTURAL PRODUCTION PRACTICES ADOPTION VIS-À-VIS SOCIO-ECONOMIC AND ICT DETERMINANTS - Manan Aslam; Zhiwen Li (Journal of Animal and Plant Sciences, 2024)
Organic agricultural production practices are generally often regarded environmentally and eco-friendly compared to conventional methods, primarily because they prevent the use of synthetic pesticides, herbicides, and fertilizers that may have untoward effects on human health and the environment. It lessens the risk of chemical residues in soil and food. Farmers' decision about organic farming practices is important due to several factors mainly the consumer demand for organic products continues to rise, organic farmers often receive premium prices for their produce and potentially enhance their own economic viability. So, the farmers' decision play an imperative role in the adoption and diffusion of organic farming practices. However, these factors and their effects remain untapped for the organic production practices. The study identified the factors affecting farmers’ decision to adopt organic production technology particularly in context of socio-economic and information and communication technologies (ICTs). A sample of 300 respondents were selected by using a purposive random sampling technique from villages of Lahore Pakistan. The outcomes obtained through the multinomial regression technique revealed that literacy level of farmers, access to ICT tools, access to credit, membership in farmers association, contact with food super stores, no use of chemicals, participation of farmers in training programs were influencing the farmers’ adoption decision to adopt organic production practices significantly. Thus, the research recommends that government officials, policy makers, farming community and agribusiness value chain actors should consider these traits when promoting smart agricultural practices to improve the well-being of associated stakeholders. Certainly, initiating awareness campaigns and pilot projects with joint involvement of public and private sectors may be highly effective in educating farming communities. Ultimately, the outcomes of this research work may navigate behavioral and cognitive dynamics to facilitate the adoption of organic production practices within the farming community.
Keywords: ICT tools; organic production technology; smart agricultural practices; agribusiness value chain; farmers association